2007
DOI: 10.1002/cphc.200600757
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Dependence of the Optical Rotation in Six Bicyclic Organic Molecules Calculated by Vibrational Averaging

Abstract: The vibrational corrections and the temperature dependence of the specific rotation of six rigid organic molecules (alpha-pinene, beta-pinene, cis-pinane, camphene, camphor, and fenchone) were calculated at three wavelengths using hybrid time-dependent density functional theory (TDDFT). A technique for calculating the temperature dependence of the vibrational average of a molecular property has been applied to obtain the specific rotation of the molecules as a function of temperature. For cases in which accura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 63 publications
1
43
0
Order By: Relevance
“…The calculated ORD [45]. Likewise, the incorporation of vibrational averaging for six conformational rigid molecules did not improve the prediction of the optical rotation, maybe since the calculations were performed in vacuo and the experimental data were obtained in ethylcyclohexane [46]. Therefore, typical polarization effects of the solvent were neglected.…”
Section: Ordmentioning
confidence: 97%
See 1 more Smart Citation
“…The calculated ORD [45]. Likewise, the incorporation of vibrational averaging for six conformational rigid molecules did not improve the prediction of the optical rotation, maybe since the calculations were performed in vacuo and the experimental data were obtained in ethylcyclohexane [46]. Therefore, typical polarization effects of the solvent were neglected.…”
Section: Ordmentioning
confidence: 97%
“…Therefore, typical polarization effects of the solvent were neglected. In addition, Mort and Autschbach [46] concluded that the incorporation of vibrational effects on the ORD might not be sufficient to obtain accurate results as exemplified for methyloxirane and methylnorbornanone. A publication on the gas phase optical rotation of limonene demonstrated that very small amounts of analyte can be measured: a detection limit of 20 ng was determined [47].…”
Section: Ordmentioning
confidence: 99%
“…Vibrational effects are generally non-neglible [21][22][23][24][25][26] and have been shown to account for as much as 20% of the optical rotation of rigid molecules. 22 In the case of methyloxirane, vibrational effects must be taken into account to reproduce the experimental gas phase optical rotation to within a few degrees.…”
Section: Introductionmentioning
confidence: 99%
“…[14,16] This program can be easily interfaced with a number of standard quantum chemistry packages and computational models (density functional theory, correlated ab initio, Hartree-Fock, and semi-empirical methods) as long as energy gradients and the property P are available analytically. The vibrational corrections of a molecular property P and their temperature-dependence is modeled with an expression that includes the first order effects due to the anharmonicity of the potential energy surface and the curvature of the property surface, Equation (1):…”
Section: Vibrational Averagingmentioning
confidence: 99%
“…[18,19] We have recently reported a generally applicable and relatively simple protocol for calculating the temperature dependence of a molecular property based on vibrational averaging. [14] This technique has been applied to the calculation of the intrinsic vibrational temperature dependence of optical rotation in organic molecules, [15,16] H-D spin-spin coupling constants in metal complexes, [14] and the Verdet constants of small molecules. [17] Two fields of application where vibrational corrections have turned out to be important are optical activity and NMR parameters.…”
Section: Introductionmentioning
confidence: 99%